1998
DOI: 10.1136/thx.53.8.685
|View full text |Cite
|
Sign up to set email alerts
|

Increases in CD4+ T lymphocytes, macrophages, neutrophils and interleukin 8 positive cells in the airways of patients with bronchiectasis

Abstract: Background-Bronchiectasis is a chronic suppurative lung disease characterised by irreversible dilation of the bronchi and persistent purulent sputum. The immunopathology of the disease was studied using a quantitative immunostaining technique with particular reference to T lymphocytes, macrophages, and granulocytes. (Thorax 1998;53:685-691) Methods-Bronchial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 28 publications
3
89
0
4
Order By: Relevance
“…The number of CD4+ lymphocytes is also increased in parallel with the number of neutrophils in the airways of patients with COPD (55,56) and exposure to cigarette smoke causes recruitment of neutrophils and CD4+ lymphocytes in rodent airways (57). A recent study shows an increased number of CD4+ lymphocytes and neutrophils in bronchial tissue from patients with bronchiectasis as well (58). There is also evidence that CD4+ lymphocytes have a functional impact; the presence of CD4+ lymphocytes is related to bronchial reactivity in murine and in human airways in vivo, but it is not known whether this phenomenon depends upon orchestration of eosinophils or neutrophils or both (59)(60)(61).…”
Section: T-lymphocytes and Neutrophilic Airway Inflammationmentioning
confidence: 99%
“…The number of CD4+ lymphocytes is also increased in parallel with the number of neutrophils in the airways of patients with COPD (55,56) and exposure to cigarette smoke causes recruitment of neutrophils and CD4+ lymphocytes in rodent airways (57). A recent study shows an increased number of CD4+ lymphocytes and neutrophils in bronchial tissue from patients with bronchiectasis as well (58). There is also evidence that CD4+ lymphocytes have a functional impact; the presence of CD4+ lymphocytes is related to bronchial reactivity in murine and in human airways in vivo, but it is not known whether this phenomenon depends upon orchestration of eosinophils or neutrophils or both (59)(60)(61).…”
Section: T-lymphocytes and Neutrophilic Airway Inflammationmentioning
confidence: 99%
“…Previous studies have shown the presence of intense inflammatory activity characterized by neutrophils, T-cells and interleukin (IL)-8 positive cells and elevated levels of IL-6, IL-8, tumour necrosis factor (TNF)-α, leukotriene B4, endothelin 1, elestase in sputum and bronchoalveolar lavage samples of bronchiectasis patients (7)(8)(9)(10)(11)(12). Recent evidence suggests the presence of systemic inflammation in chronic inflammatory airway diseases.…”
Section: Does Airway Colonization Cause Systemic Inflammation In Bronmentioning
confidence: 99%
“…Furthermore, exposure to cigarette smoke causes accumulation of CD4+ lymphocytes and neutrophils in the bronchoalveolar space of guinea pigs in vivo [137]. There is also accumulation of CD4+ lymphocytes and neutrophils in airway tissue from patients with bronchiectasis [36]. The accumulation of CD4+ lymphocytes is even associated with functional changes in the lungs; the local presence of CD4+ lymphocytes is related to nonspecific bronchial hyperreactivity in humans, mice and rats in vivo, even though it is not known whether this phenomenon is linked to the orchestration of neutrophils or eosinophils [129,130,[138][139][140].…”
Section: T-lymphocytes and Neutrophil Mobilisationmentioning
confidence: 99%